Influence of fracture toughness on vacuum hardened HSS - Leskovšek, Vojteh (Kovine zlitine tehnologije, 1995)
Fractures, macro-chipping and micro-chipping are all effects by which curtting edges are destroyed. The ability of a steel to resist these phenomena is known as its toughness. HSS, however, possess an appreciable ductility, although the notched or even unnotched specimens tested in the pendulum test are not sensitive enough to discriminate between high and low levels of toughness. Therefore, it becomes important to use a method of testing which can detect small variations in ductility. To establish the fracture toughness, the round-notched tensile specimens with a fatigue crack at the notch root was used. Fatiguing was done in as soft annealed condition. After that, the vacuum heat treatment for the achievement of optimal working properties was carried out and the final testing was performed. Our experiments confirm that the correlation based on the round-notched tension test can be successfully used to calculate the critical fracture toughness. On the basis of the above-mentioned experimental results, we were able to compose a diagram which simultaneously scoops the technological parameters of vacuum heat-treatment, the mechanical properties and the micro structure of vacuum heat-treated HSS M2.
Keywords: jeklo; žilavost; trdota; vakuumska obdelava